Effects of Walking Endurance Reduction on Gait Stability in Patients with Stroke. (28th September 2011) - Iosa, M.; Morone, G.; Fusco, A.; Pratesi, L.; Bragoni, M.; Coiro, P.; Multari, M.; Venturiero, V.; De Angelis, D.; Paolucci, S.
Abstract : Control of gait is usually altered following stroke, and it may be further compromised by overexertion and fatigue. This study aims to quantitatively assess patients' gait stability during six-minute walking, measuring upper body accelerations of twenty patients with stroke (64 ± 13 years old) and ten age-matched healthy subjects (63 ± 10 years old). Healthy subjects showed a steady gait in terms of speed and accelerations over the six minutes. Conversely, the patients unable to complete the test (n = 8 ) progressively reduced their walking speed (−22 ± 11 %, confidence interval CI95% : −13, −29%, P = 0.046 ). Patients able to complete the test (n = 12 ) did not vary their walking speed over time (P = 0.493 ). However, this ability was not supported by an adequate capacity to maintain their gait stability, as shown by a progressive increase of their upper body accelerations (+5 ± 11 %, CI95% : −1; +12%, P = 0.010 ). Walking endurance and gait stability should be both quantitatively assessed and carefully improved during the rehabilitation of patients with stroke.